(3GdQSGdI GdefaPg Edi GdbGVis - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3ef YHO CejQ GdeDefjf heedhcg MeRg Hf Ydi Hf CMeO CeG HYO abO JbOeJ dfG Edjc QSGdI fSCdc Yf eYQaJc HfaSc abUQJ Yf GdELGHI s
(3BNQgG (B:s
(3aGfXQ dfaSc abO CYPQJc eQI HYO CNQi hCfPQJc hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B29s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds